Nasalance during use of pharyngeal and glottal place of production - Garcia, Ariany Fernanda; Marino, Viviane Cristina de Castro [UNESP]; Pegoraro-Krook, Maria Inês; Guerra, Thais Alves; Lauris, José Roberto Pereira; Dutka, Jeniffer de Cassia Rillo (FapUNIFESP (SciELO), 2014)
This study obtained nasalance scores during use of compensatory articulation (CA) and compared nasalance between groups with and without hypernasality and with and without CA. Speech samples were obtained from 43 individuals with and without velopharyngeal dysfunction during repetition of 20 phrases originating 860 audio recordings and their respective nasometric values. After excluding 143 recordings due to low quality, the remaining 717 samples were rated by three speech language pathologists (SLPs), independently, for presence or absence of hypernasality and CA. Nasalance scores for the 553 samples rated with 100% agreement among the SLPs were grouped according to the auditory-perceptual ratings: Group 1 (G1) - included samples without hypernasality and without CA (n=191); Group2 (G2) - included samples with hypernasality and without CA (n=288); Group 3 (G3) - included samples with hypernasality and with pharyngeal fricative (n=33); Group 4 (G4) - included samples with hypernasality and with glottal stop (n=41). Analysis of variance (ANOVA) revealed significant difference nasalance scores which were significantly higher for G2, G3, and G4 (p<0.0001) when compared to G1. The use of pharyngeal fricative (G3), particularly during /f/ (p=0.0018) and /s/ (p=0.0017) productions resulted in nasalance scores significantly higher than scores found for G2. Significantly higher nasalance values where identified during use of pharyngeal fricative.

Objetivo: Este estudo obteve medidas de nasalância durante a produção de articulação compensatória (AC) e comparou a nasalância entre grupos com e sem hipernasalidade e com e sem AC. Métodos: As amostras de fala foram obtidas a partir de 43 indivíduos com e sem disfunção velofaríngea durante a repetição de 20 frases, originando um total de 860 gravações e respectivos valores nasométricos. Foram excluídas 143 gravações devido à baixa qualidade e as 717 amostras restantes foram avaliadas por três fonoaudiólogas, de forma independente, quanto à presença ou ausência de hipernasalidade e AC. As 553 amostras julgadas com 100% de concordância entre as fonoaudiólogas foram agrupadas de acordo com o julgamento perceptivo-auditivo: Grupo 1 (G1) - amostras sem hipernasalidade e sem AC (n=191); Grupo 2 (G2) - amostras com hipernasalidade e sem AC (n=288); Grupo 3 (G3) - amostras com hipernasalidade e com fricativa faríngea (n=33); Grupo 4 (G4) - amostras com hipernasalidade e com oclusiva glotal (n=41). Resultados: Análise de variância (ANOVA) revelou medidas de nasalância significativamente maiores para G2, G3 e G4 (p<0,0001) quando comparados ao G1. O uso de fricativa faríngea (G3), particularmente durante /f/ (p=0,0018) e /s/ (p=0,0017) resultou em valores de nasalância significativamente maiores que os valores encontrados para G2. Conclusão: Valores de nasalância significativamente mais elevados foram encontrados durante produção de fricativa faríngea.
Nasalância durante produção de fricativa faríngea e oclusiva glotal
Keywords: Speech; Cleft palate; Speech disorders; Speech production measurement; Speech, language and hearing sciences; Fala; Fissura palatina; Distúrbios da fala; Medida da produção da fala; Fonoaudiologia